2008
DOI: 10.1002/jmv.21128
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological analysis of a nosocomial outbreak of respiratory syncytial virus associated pneumonia in a kangaroo mother care unit in South Africa

Abstract: Respiratory syncytial virus (RSV) may cause severe lower respiratory tract disease in premature infants. Prolonged viral shedding has been reported in patients with underlying immunosuppressive disorders, such as human immunodeficiency virus 1 (HIV-1) infection. During March to May 2006, 23 preterm pediatric patients developed nosocomial pneumonia in a district hospital in the Gauteng Province of South Africa due to RSV infection. The patients were identified using routine diagnostic testing. All had been admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 45 publications
2
20
1
5
Order By: Relevance
“…The epidemiological data from Madrid examined in this work, together with the data in recent publications (1,7,48,55,57,68,75), indicated that BA viruses have gradually replaced the rest of the group B genotypes (Fig. 2).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The epidemiological data from Madrid examined in this work, together with the data in recent publications (1,7,48,55,57,68,75), indicated that BA viruses have gradually replaced the rest of the group B genotypes (Fig. 2).…”
Section: Discussionsupporting
confidence: 70%
“…Unique partial G sequences (nucleotides 510 to 981) with a 60-nt duplication obtained from clinical samples collected in Madrid (Table 1) Since epidemiologic information was available for seven places (including Madrid) (7,26,48,55,64,67,68,75), the prevalences of both HRSV group B and the BA genotype were examined in these locations (Fig. 2).…”
Section: Fig 1 Phylogenetic Tree Of Hrsv-b Sequences Frommentioning
confidence: 99%
“…Since then, these BA strain viruses have become the prominent circulating B strains (79)(80)(81)(82)(83)(84)(85). More recently, an A strain with a 72-nucleotide duplication in the C-terminal third of its G protein has become a predominant circulating A strain (79-81, 83, 85-87).…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 seroprevalence among mothers of these infants was 52.6%, suggesting a high level of perinatal exposure (25). Here, we describe identification of G protein deletion mutants that were significantly reduced in size in comparison to that of prototype controls in children with pneumonia.…”
mentioning
confidence: 86%